Decreased secretion of Paneth cell α‐defensins in graft‐versus‐host disease. Issue 5 (26th September 2015) - Eriguchi, Y.; Nakamura, K.; Hashimoto, D.; Shimoda, S.; Shimono, N.; Akashi, K.; Ayabe, T.; Teshima, T.
Abstract Background Intestinal microbial ecology is actively regulated by Paneth cell‐derived antimicrobial peptides, α‐defensins. Graft‐versus‐host disease (GVHD) is a major complication of allogeneic hematopoietic stem cell transplantation (SCT). We previously demonstrated that Paneth cells are targeted by GVHD, and their expression of antimicrobial peptide α‐defensins is impaired, leading to a loss of physiological diversity among the microflora and development of bloodstream infection. Herein, we evaluated whether fecal levels of α‐defensins could be surrogate marker of intestinal dysbiosis. Methods We directly measured α‐defensin cryptdin‐1 (Crp1) in fecal pellets of mice with GVHD by using a novel enzyme‐linked immunosorbent assay. Results Fecal levels of Crp1 were significantly decreased in mice with GVHD but unchanged in mice without GVHD after SCT. These were correlated with intestinal flora diversity. Conclusion We demonstrate a link between reduced secretion of Paneth cell α‐defensins and dysbiosis of intestinal flora in GVHD. Fecal levels of α‐defensins could be surrogate markers for intestinal microbial homeostasis.